Statebuilding and narrative - Da Silva, R.; Graef, J. (Handbook on intervention and statebuilding, 2019)
In recent years, narrative approaches have become increasingly popular in the study of peaceand statebuilding. Yet, the conceptual and empirical idiosyncrasies of stories and storytelling are rarely acknowledged. This chapter provides an overview of the uses of narrative in the field to date. It highlights its value for understanding power imbalances, the complexity of human experiences and knowledge creation, and ethical challenges connected to fieldwork. Engaging in greater depth with conceptual and analytical perspectives on narrative, not least by drawing on insights from related social science disciplines, will help to uncover the unique contribution these perspectives can make to researching and practicing peace- and statebuilding.